Determinants of financial inclusion in small and medium enterprises: Evidence from Ethiopia - Betgilu Oshora; Goshu Desalegn; Eva Gorgenyi-Hegyes; Maria Fekete-Farkas; Zoltan Zeman (Journal of Risk and Financial Management, 2021)
The study examines the determinant factors that influence financial inclusion among small and medium enterprises (SMEs) in Ethiopia. The study uses an explanatory research design and a mixed research approach with both primary and secondary sources of data. More specifically, the study adopts a multiple linear regression model. The finding of the study reveals that; supply-side factors, demand-side factors, market opportunity, and collateral requirements have a positive effect on the firm's access to finance. On the other hand, institutional framework factors, and the costs of borrowing negatively affect the firm's access to finance. This study suggests concerned bodies sustain rapid and inclusive economic growth and hence eradicate extreme poverty and hunger, the policymakers must build an efficient, strong, and well-functioning financial market system that provides affordable and sustainable financial service to SMEs.
Keywords: 330; access to finance; collateral requirements; cost of borrowing; Ethiopia; financial inclusion; SMEs